Faktoren, die das energiesparende Verhalten beeinflussen - Tanja Engelmann; Michelle Götz; Jessica Weiler; Anton Würth (Books on Demand (BoD), 2024)
The importance of energy-saving behaviour has become crucial due to recent negative events. The current empirical study investigates the factors that influence such behaviour. Hypotheses based on the revised theory of planned behaviour (Ajzen, 2020: 314f.) were formulated to examine the relationships between different influencing factors. An online questionnaire was used to gather data from 158 participants. The results widely confirmed the assumptions of the revised theory of planned behaviour. Among other results, the study showed that attitude towards energy-saving behaviour and the subjective norm significantly predict the intention to save energy. In addition, this intention explains energy-saving behaviour.
Keywords: 650; Energieeinsparung; Faktorenanalyse; Befragung; Konsumentenverhalten; Deutschland; Energieeinsparung; Faktorenanalyse; Befragung; Konsumentenverhalten; Deutschland